Bleeding after cardiovascular surgery caused by detergent residues in laparotomy sponges - Geiss, Heinrich K.; Schmitt, Judith; Frank, Stefan C. (Infection control and hospital epidemiology, 1997)
On 2 successive days in July 1994, six patients who underwent coronary artery bypass grafting developed postoperative bleeding requiring reexploration. The cause was the use of reprocessed laparotomy sponges with retained detergents, inducing a bleeding disorder.